Pengaruh Variasi Temperatur Air 7°C, 17°C, dan 27°C Pada Campuran Beton Terhadap Nilai Kuat Tekan Beton Struktural - Indriyani, Niken; Rifqi, Mirza Ghulam; Khomari, M. Galuh (Indonesian Society of Applied Science, 2021)
This study discusses the effect of water temperature variations of 7°C, 17°C, and 27°C on concrete mixes on compressive strength values ​​of structural concrete. Concrete is a material that is often used in civil engineering construction. The use of concrete in large volumes causes the heat temperature of the hydration reaction to increase. It is necessary to monitor the temperature of the water in the concrete mixture to reduce the excess heat due to the hydration reaction. Water temperature is adjusted according to the planned temperature of 7°C, 17°C, and 27°C to determine the effect on the compressive strength and workability values. Concrete compressive strength testing is carried out at 3, 7, 14, and 28 days. The number of specimens needed was 36 cylindrical samples with a diameter of 15 cm and a height of 30 cm. The results of slump testing at 7°C, 17°C, and 27°C respectively 3 cm, 5 cm and 10 cm. And for testing the compressive strength of concrete obtained data respectively 30.06 MPa, 35.31 MPa and 45.09 MPa. Increased compressive strength of concrete in each variation of 0.2%, 17.7% and 24.3%.